The photodynamic activity of a novel porphyrin derivative bearing a fluconazole structure in different media and against Candida albicans - Mora, Sabrina Jimena (2010)
The spectroscopic properties and photodynamic activity of a novel porphyrin covalently linked to an antifungal fluconazole structure were investigated in DMF and different biomimetic systems, results being compared with those obtained for the non-fluconazole homologoue. Absorption and fluorescence studies indicated that the tetrapyrrolic macrocycle retained its individual spectroscopic properties. Photosensitization ability was first evaluated using 9,10-dimethylanthracene; in microheterogenic media, the porphyrin interacted with sodium bis(2-ethylhexyl)sulfosuccinate reverse micelles and also β-cyclodextrin, photosensitized decomposition of l-tryptophan being observed in these systems. The in vitro photodynamic activity of the photosensitizers when associated with β-cyclodextrin, as tested against Candida albicans, revealed that growth delays imparted by fluconazole alone and the unsubstituted porphyrin were almost additive when the two compounds were used together. However, when the fluconazole was covalently linked to a porphyrin nucleus and exposed to light, reduction in growth delay efficacy was observed relative to the mixed system.